(untitled) (SAARC Journal of Agriculture, 2019)
The nutrient profile of five freshwater fish species viz., Mystus vittatus, Ompok bimaculatus, Channa striata, Wallago attu and Pangasianodon hypophthalmus were studied. The proximate composition data shows that the moisture and fat content differed significantly (P<0.01) among the fish species. The fat content was significantly higher in P. hypophthalmus and M. vittatus. The moisture was significantly higher in C. striata. The potassium content was significantly (p<0.01) higher in C.striata. M.vittatus shows higher content of calcium. The other trace minerals like iron, copper and zinc contents of fish did not differ significantly among the species. The vitamin A content is maximum in O.bimaculatus whereas vitamin D content is higher in Mystus vittatus. The palmitic acid was significantly (p<0.01) higher in M. vittatus. The oleic acid was significantly (p<0.01) higher in C. striata and W. attu. The linoleic acid content was significantly (p<0.05) higher in P. hypophthalmus. One of the important PUFA i.e. DHA was significantly higher in O. bimaculatus and C.striata. The PUFA content was significantly (p<0.05) higher in O.bimaculatus and P.hypophthalmus. Among the amino acids, arginine, histidine, threonine and isoleucine were higher in P.hypophthalmus. C.striata and W. attu contain high amount of Tryptophan. Glutamic acid was high in O.bimaculatus and Aspartic acid was high in C. striata. The energy content was maximum in P. hypophthalmus. The nutrient profile of these fish species revealed that they were rich in all the essential nutrients required by human being. The information on nutrient profile of fish will give a guideline to dieticians, nutritionists, medical practitioners, researchers to advice consumers to take fish in their daily diet as a health food. SAARC J. Agri., 16(2): 25-41 (2018)